The Role of Slr0151, a Tetratricopeptide Repeat Protein from Synechocystis sp. PCC 6803, during Photosystem II Assembly and Repair - Rast, Anna; Rengstl, Birgit; Heinz, Steffen; Klingl, Andreas; Nickelsen, Jörg (Frontiers in Plant Science, 2016)
The assembly and repair of photosystem II (PSII) is facilitated by a variety of assembly factors. Among those, the tetratricopeptide repeat (TPR) protein Slr0151 from Synechocystis sp. PCC 6803 (hereafter Synechocystis) has previously been assigned a repair function under high light conditions (Yang et al., 2014). Here, we show that inactivation of slr0151 affects thylakoid membrane ultrastructure even under normal light conditions. Moreover, the level and localization of Slr0151 are affected in a variety of PSII-related mutants. In particular, the data suggest a close functional relationship between Slr0151 and Sll0933, which interacts with Ycf48 during PSII assembly and is homologous to PAM68 in Arabidopsis thaliana. Immunofluorescence analysis revealed a punctate distribution of Slr0151 within several different membrane types in Synechocystis cells.